Inovasi Pembangunan Rocket Stove di Desa Wangisagara untuk Solusi Sampah - Herpiyanti, Linda (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
The Community Service Program (KKN) of Langlangbuana University, Group 18, conducted in Wangisagara Village, Majalaya District, Bandung Regency, focused on addressing issues related to waste management facilities. The program introduced an innovative solution through the construction of a rocket stove, a waste incineration device designed to minimize smoke emissions. The methods implemented included field observations, community interviews, the construction of rocket stove, and the preparation of a user manual. The Rocket stove effectively reduced the volume of smoke produced during waste burning due to its combustion chamber design, which oprimizes the burning process. The implications of this program include a significant reduction in air pollution and an increase in community awareness of simple yet effective innovations in waste management.